The naturalness of Chinese online chatting: Organization and recontextualization - Chen, Xinren; Chen, Tiancheng (Frontiers in Communication, 2023)
Two-party or multi-party typed chatting on social media platforms is becoming a popular object of study in pragmatic research nowadays. Apparently, such chatting is very often non-synchronous and non-spontaneous and thus is arguably not so naturally occurring. However, based on a close examination of some details of WeChat typed talk (WTT) among Chinese, the present study seeks to demonstrate that in terms of organization and recontextualization, WTT is naturally occurring in some common as well as distinctive ways and thus amenable to digital conversation analysis (CA). It is hoped that this study may contribute to the understanding of online typed chatting and provide further justification for adopting digital conversation analysis in the study of online typed chatting for performing social actions.